Electronic cigarette use among 14- to 17-year-olds in Europe. (20th October 2020) - Kinnunen, Jaana M; Rimpelä, Arja H; Lindfors, Pirjo L; Clancy, Luke; Alves, Joana; Hoffmann, Laura; Richter, Matthias; Kunst, Anton E; Lorant, Vincent
Abstract: Background: Studies comparing adolescent e-cigarette use in different countries are scarce. We study students' e-cigarette and conventional cigarette ever-use, their social correlates and e-liquid use in seven EU countries. Methods: SILNE-R data ( N =12 167, response rate 79.4%) of 14–17-year-olds from Amersfoort (NL), Coimbra (PT), Dublin (IR), Hanover (GE), Latina (IT), Namur (BE) and Tampere (FI) were used. E-cigarette and conventional cigarette ever-use, dual-use, type of e-liquid and social correlates were measured with a school survey and analyzed with cross-tabulations and multinomial logistic regression. Results: About 34% had tried e-cigarettes, but the variation was large between the cities (Latina 50%; Hanover 23%). Of e-cigarette ever-users, 37% had used nicotine e-liquid, 43% exclusively non-nicotine liquid and 20% did not know the content. Nicotine e-liquid was more prevalent among monthly e-cigarette users and weekly smoking e-cigarette users. The social correlates were mainly the same for exclusive e-cigarette ever-use, exclusive conventional cigarette ever-use and dual-use. Boys had greater odds for exclusive e-cigarette and dual-use compared to girls. Of social correlates, low academic achievement and parental smoking were positively associated with all categories of use, but parental education and immigrant background were not. The strongest association was found between peer smoking (most/all best friends smoke) and dual-use (OR 34.29). Conclusions: Students' e-cigarette ever-use varies greatly between EU countries. E-cigarettes seem not to be a substitute for conventional cigarettes but more a complementary product. Tobacco control policies might also prevent e-cigarette use but specific regulations on e-cigarettes are needed to prevent nicotine addiction originating from them.